2019
DOI: 10.1177/0022466919851194
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Secondary Age Students With Intellectual Disability Who Participate in School-Sponsored Extracurricular Activities

Abstract: This study investigated the relation between grade level, support needs, and use of augmentative and alternative communication (AAC) and the participation of secondary age students with intellectual disability in school-sponsored extracurricular activities. Participants were special education teachers with at least one student with an intellectual disability on their caseload who participated in a school-sponsored extracurricular activity ( N = 498). Data were collected using an online questionnaire sent to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Research has shown that involvement in STEM-related activities such as STEM clubs predicts entry into STEM in college, the completion of advanced science and mathematics courses in high school, and students aspiring to enter a STEM career (Andersen & Ward, 2014;Maltese & Tai, 2011;Regan & DeWitt, 2015). However, SWDs do not participate in extracurricular activities as much as their nondisabled peers (Dymond et al, 2020; U.S. Department of Education, Office for Civil Rights, 2013). As a result, the present study aimed to investigate student and parent perceptions about the influences on and challenges to SWDs' participation in STEM clubs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that involvement in STEM-related activities such as STEM clubs predicts entry into STEM in college, the completion of advanced science and mathematics courses in high school, and students aspiring to enter a STEM career (Andersen & Ward, 2014;Maltese & Tai, 2011;Regan & DeWitt, 2015). However, SWDs do not participate in extracurricular activities as much as their nondisabled peers (Dymond et al, 2020; U.S. Department of Education, Office for Civil Rights, 2013). As a result, the present study aimed to investigate student and parent perceptions about the influences on and challenges to SWDs' participation in STEM clubs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ever-increasing demands of class time, many SWDs have their interest in STEM met after school through extracurricular activities (Afterschool Alliance, 2016). Past research has shown the positive impact of extracurricular activities on student development (Berger et al, 2020;Blanchard et al, 2020;Ricci et al, 2020) and previous studies indicate participation in inquiry-based afterschool STEM programs show positive gains (Dymond et al, 2020;Makitalo-Siegl et al, 2011). In addition, Cutucache and colleagues (2018) found an increase in STEM content knowledge in participants of an afterschool STEM club.…”
Section: Informal or Extracurricular Stem Activities Help Bridge The Gapmentioning
confidence: 93%
See 1 more Smart Citation
“…The development of this experience raises new challenges and objectives. Boosting and stabilizing the presence of people with functional diversity in non-formal education activities (Dymond et al, 2020) would require the presence of experts in the working groups to advise on the measures needed to create truly inclusive spaces. However, it would also be necessary to promote studies such as those carried out by Pita-Carmo and Massarani (2022a) to highlight the preferences and demands of the population who encounter barriers to access and participation so the organizations responsible for these spaces and activities can incorporate them.…”
Section: Final Conclusionmentioning
confidence: 99%
“…The broad array of courses, extracurricular activities, school-sponsored events, and social opportunities available during middle and high school offer a rich context for learning and relationships. Unfortunately, access to these myriad experiences-within and beyond the classroom-remains uneven for many secondary students with IDD (Agran et al, 2020;Dymond et al, 2020). Educators need effective strategies and supports to ensure students with IDD benefit from the important instructional and interpersonal experiences available throughout their schools.Peers provide an especially promising pathway for supporting access to the abundance of experiences offered during secondary school.…”
mentioning
confidence: 99%